2014
DOI: 10.1002/brb3.172
|View full text |Cite
|
Sign up to set email alerts
|

Fgf2 improves functional recovery—decreasing gliosis and increasing radial glia and neural progenitor cells after spinal cord injury

Abstract: ObjectivesA major impediment for recovery after mammalian spinal cord injury (SCI) is the glial scar formed by proliferating reactive astrocytes. Finding factors that may reduce glial scarring, increase neuronal survival, and promote neurite outgrowth are of major importance for improving the outcome after SCI. Exogenous fibroblast growth factor (Fgf) has been shown to decrease injury volume and improve functional outcome; however, the mechanisms by which this is mediated are still largely unknown.MethodsIn th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 45 publications
8
73
3
1
Order By: Relevance
“…Observers have included non-neurological medical practitioners, nurses, speech pathologists and neuroscientists, and indeed the author of this editorial. A parallel outcome has apparently been reported independently (https://www.youtube.com/ watch?v=VGuBMroX7c8) by a Stanford group [10] by injecting stem cells known to generate a cytokine with anti-TNF activity into the brain [11,12]. These as yet uncontrolled observations reinforce each other, and are both highly plausible from the TNF literature.…”
Section: Authors Unaware Of Literature On Rapid Long-lasting Responssupporting
confidence: 72%
“…Observers have included non-neurological medical practitioners, nurses, speech pathologists and neuroscientists, and indeed the author of this editorial. A parallel outcome has apparently been reported independently (https://www.youtube.com/ watch?v=VGuBMroX7c8) by a Stanford group [10] by injecting stem cells known to generate a cytokine with anti-TNF activity into the brain [11,12]. These as yet uncontrolled observations reinforce each other, and are both highly plausible from the TNF literature.…”
Section: Authors Unaware Of Literature On Rapid Long-lasting Responssupporting
confidence: 72%
“…A previous report that evaluated the effect of FGF2 in a hemisection rat SCI model indicated that the effect of FGF2 on SCI is related to inhibited inflammation, lower production of CSPG, and increased glial processes. 5 However, the effect of FGF2 on SCI was associated with the proliferation, morphogenesis, and apoptosis of various cell populations, particularly astrocytes and neural cells, via complex signal transduction pathways in these studies. [6][7][8] The beneficial effects of FGF2 on SCI were correlated with neuronal regeneration and functional recovery.…”
Section: Introductionmentioning
confidence: 82%
“…This indicates dual roles for bFGF in regulating GFAP expression in vivo between immature and mature CNS tissue. Concurrent with the effects bFGF has on GFAP expression in astrocytes, it has been implicated in regulating and promoting neuronal differentiation during fetal development [209] and survival post traumatic injury [210] (for a brief review of bFGF effects post CNS injury see Adeeb & Mortazavi [47]). Thus, the effect of bFGF on cultured astrocytes and neurons is paradoxical promoting a reactive astrocyte phenotype however simultaneously promoting neuronal survival.…”
Section: Neuron-glia Culturesmentioning
confidence: 99%
“…These changes are in part regulated by an array of growth factors, cytokines and chemokines. Growth factors include fibroblast growth factors (FGF) and receptors (FGFR) [24,45,46], and transforming growth factor-b (TGF-b) and receptors [26,39], while the principle cytokines and chemokines include tumor necrosis factor alpha (TNFa) [47] and interleukins [26]. The complex interplay of these and other factors dynamically regulate the microenvironment of the lesion penumbra, which can either preserve function or lead to dysfunction; such changes occur due to promotion or inhibition of the neural network and glial cell remodeling, respectively.…”
Section: In Vivo Responses To Traumatic Brain Injurymentioning
confidence: 99%